Artemisia argyi Essential Oil Inhibits Hepatocellular Carcinoma Metastasis via Suppression of DEPDC1 Dependent Wnt/β-Catenin Signaling Pathway - Li, Yanli; Tian, Yang; Zhong, Wei; Wang, Ning; Wang, Yafeng; Zhang, Yan; Zhang, Zhuangli; Li, Jianbo; Ma, Fang; Zhao, Zhihong; Peng, Youmei (Frontiers in Cell and Developmental Biology, 2021)
The tumor metastasis is the major hurdle for the treatment of advanced hepatocellular carcinoma (HCC), due in part to the lack of effective systemic treatments. DEPDC1, a novel oncoantigen upregulated in HCC, is thought to be a molecular-target for novel therapeutic drugs. Artemisia argyi is a traditional Chinese medicine with anti-inflammatory and anti-tumor activities. This study investigated the potential therapeutic benefits of Artemisia argyi essential oil (AAEO) in suppressing metastasis of HCC by targeting DEPDC1. Assessment of AAEO cytotoxicity was performed by MTT assay. Anti-metastatic effects of AAEO were investigated in vitro using wound healing and transwell assays. The HepG2 cells were transduced with lentiviral vector containing luciferase (Luc). A metastasis model of nude mice was established by tail vein injection of HepG2-Luc cells. The nude mice were treated with AAEO (57.5, 115 and 230 mg/kg) or sorafenib (40 mg/kg). Metastasis of HCC cells was monitored via in vivo bioluminescence imaging. After treatment for 21 days, tissues were collected for histological examination and immunohistochemistry analysis. Gene and protein levels were determined by real-time quantitative PCR and western blotting. The results revealed that AAEO significantly inhibits the migration and invasion in vitro in a concentration-dependent manner. In vivo assays further confirmed that AAEO markedly inhibits HCC metastasis into lung, brain, and femur tissues and exhibits low toxicity. Our results suggested that AAEO signiﬁcantly downregulates the mRNA and protein expression of DEPDC1. Also, AAEO attenuated Wnt/β-catenin signaling through reduction of Wnt1 and β-catenin production. Moreover, AAEO prevented epithelial-mesenchymal transition (EMT) by downregulation of vimentin and upregulation of E-cadherin. Furthermore, we found that DEPDC1 promoted HCC migration and invasion via Wnt/β-catenin signaling pathway and EMT. These results demonstrate that AAEO effectively inhibits HCC metastasis via attenuating Wnt/β-catenin signaling and inhibiting EMT by suppressing DEPDC1 expression. Thus, AAEO likely acts as a novel inhibitor of the DEPDC1 dependent Wnt/β-catenin signaling pathway.